Efficacy of the Radical Scavenger, Tempol, to Reduce Inflammation and Oxidative Stress in a Murine Model of Atopic Dermatitis - Alessio Ardizzone; Alberto Repici; Anna Paola Capra; Federica De Gaetano; Valentina Bova; Giovanna Casili; Michela Campolo; Emanuela Esposito (MDPI AG, 2023)
Atopic dermatitis (AD) is the most common chronically relapsing inflammatory skin disease, predominantly common in children; it is characterized by an eczematous pattern generally referable to skin dryness and itchy papules that become excoriated and lichenified in the more advanced stages of the disease. Although the pathophysiology of AD is not completely understood, numerous studies have demonstrated the complex interaction between genetic, immunological, and environmental factors, which acts to disrupt skin barrier function. Free radicals play a key role by directly damaging skin structure, inducing inflammation and weakening of the skin barrier. Tempol (4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl) is a membrane-permeable radical scavenger, known to be a stable nitroxide, which exhibits excellent antioxidant effects in several human disorders, such as osteoarthritis and inflammatory bowel diseases. Considering the few existing studies on dermatological pathologies, this study aimed to evaluate tempol, in a cream formulation, in a murine model of AD. Dermatitis was induced in mice via dorsal skin application of 0.5% Oxazolone, three times a week for two weeks. After induction, mice were treated with tempol-based cream for another two weeks at three different doses of 0.5%, 1% and 2%. Our results demonstrated the ability of tempol, at the highest percentages, to counteract AD by reducing the histological damage, decreasing mast cell infiltration, and improving the skin barrier properties, by restoring the tight junction (TJs) and filaggrin. Moreover, tempol, at 1% and 2%, was able to modulate inflammation by reducing the nuclear factor kappa-light-chain-enhancer of the activated B cell (NF-κB) pathway, as well as tumor necrosis factor (TNF)-α and interleukin (IL)-1β expression. Topical treatment also attenuated oxidative stress by modulating nuclear factor erythroid 2-related factor 2 (Nrf2), manganese superoxide dismutase (MnSOD), and heme oxygenase I (HO-1) expression levels. The obtained results demonstrate the numerous advantages provided by the topical administration of a tempol-based cream formulation, in reducing inflammation and oxidative stress through modulation of the NF-κB/Nrf2 signaling pathways. Therefore, tempol could represent an alternative anti-atopic approach to treating AD, thereby improving skin barrier function.